1998
DOI: 10.1507/endocrj.45.241
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adrenomedullin Levels in Patients with Non-Insulin Dependent Diabetes Mellitus: Close Relationships with Diabetic Complications.

Abstract: Abstract.The present study was undertaken to determine plasma adrenomedullin levels in patients with non-insulin dependent diabetes mellitus (NIDDM) to elucidate the potential involvement in the pathogenesis of diabetic complications. The patients were 24 males and 21 females with ages of 55 ± 2.1 years (mean ± SEM). Plasma adrenomedullin levels were 5.94 ± 0.44 pmol/l in patients with NIDDM, and were not affected by plasma glucose concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…The insulin-resistant state that inexorably develops during obesity could be the source of the observed plasmatic adrenomedullin upregulation in diabetic patients (Fig. 7) (8,9,23). This is in accordance with the fact that insulin failed to inhibit adrenomedullin expression in obese and insulin-resistant ZDF rat adipocytes (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…The insulin-resistant state that inexorably develops during obesity could be the source of the observed plasmatic adrenomedullin upregulation in diabetic patients (Fig. 7) (8,9,23). This is in accordance with the fact that insulin failed to inhibit adrenomedullin expression in obese and insulin-resistant ZDF rat adipocytes (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Higher plasma levels of ADM or of MR-proADM were observed in patients with diabetic nephropathy than in patients without nephropathy in small cross-sectional Japanese and Chinese studies (25,26). However, no independent association was observed with the incidence of new cases of albuminuria in a larger Dutch study (ZODIAC) with a median follow-up of 5.6 years (27).…”
Section: Discussionmentioning
confidence: 90%
“…Epidemiological data on ADM and diabetic nephropathy are scarce (25)(26)(27). Based on what is known of the physiological effects of the peptide, we hypothesized that ADM may have a nephroprotective effect in diabetes.…”
mentioning
confidence: 99%
“…These data suggest that AM is involved in the negative regulation of insulin secretion in an autocrine/paracrine manner. Furthermore, several clinical studies have reported that plasma AM concentrations are elevated in patients with diabetes (4,5,27). In fact, it has been shown that AM infusion increased plasma glucose levels in a diabetic rat model, whereas administration of anti-AM antibody had the opposite effect and improved postprandial recovery (21).…”
Section: Discussionmentioning
confidence: 99%